Alkitab dan Tantangan Zaman: Apologetika Terhadap Agnostik dalam Konteks Kekristenan Indonesia di Era Disrupsi - Helenda Tuah (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2024)
The rapid development of the disruption era has affected various aspects of life, including religious thought, which now faces challenges from agnostic thought. Agnosticism emerges as a view that doubts the existence of God and sees religion as archaic and inhibits the progress of thinking. This phenomenon further strengthens the idea that religion is irrelevant in the context of the times. The purpose of this study is to describe the role of Christian apologetics in facing the challenges of agnostic thinking in the era of disruption. This research uses a descriptive qualitative approach with literature study as the main method. Data were obtained through the analysis of various literature sources, searching for biblical references, and studying phenomena in the field. This approach aims to provide practical solutions for Christians to remain steadfast in their faith despite the challenges of the times and agnostic thinking that can threaten their beliefs. In conclusion, biblically-grounded Christian apologetics can help Christians strengthen their faith in the midst of disruption and ensure that they maintain firm convictions in the face of contemporary ideological challenges.